2016
DOI: 10.1016/j.ecresq.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Household chaos and children’s cognitive and socio-emotional development in early childhood: Does childcare play a buffering role?

Abstract: Evidence suggests that household chaos is associated with less optimal child outcomes. Yet, there is an increasing indication that children’s experiences in childcare may buffer them against the detrimental effects of such environments. Our study aims were to test: (1) whether children’s experiences in childcare mitigated relations between household chaos and children’s cognitive and social development, and (2) whether these (conditional) chaos effects were mediated by links between chaos and executive functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
73
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 58 publications
10
73
0
4
Order By: Relevance
“…Indeed, although it failed to reach statistical significance, there was a descriptive indication that nonmaternal care was associated with better social outcomes for low-income children. We and our colleagues have recently shown similar findings with respect to child care exposure and several outcomes in pre-kindergarten (Berry et al, 2016). Specifically, we found that for children experiencing high levels of household chaos across early childhood, greater weekly hours in child care were predictive of comparatively fewer behavior problems.…”
Section: Economic Adversity Child Care and Stress Physiologysupporting
confidence: 82%
See 1 more Smart Citation
“…Indeed, although it failed to reach statistical significance, there was a descriptive indication that nonmaternal care was associated with better social outcomes for low-income children. We and our colleagues have recently shown similar findings with respect to child care exposure and several outcomes in pre-kindergarten (Berry et al, 2016). Specifically, we found that for children experiencing high levels of household chaos across early childhood, greater weekly hours in child care were predictive of comparatively fewer behavior problems.…”
Section: Economic Adversity Child Care and Stress Physiologysupporting
confidence: 82%
“…With rare exception, however, the extant findings with respect to child care and children's adrenocortical functioning have been based on studies of middle-to upper-income families (though see Rappolt-Schlichtmann et al, 2009). There is good reason to suspect that the relation between children's child care experiences and their subsequent development-behaviorally and physiologically-may be quite different for children growing up in the context of economic adversity (Berry et al, 2014(Berry et al, , 2016Côté et al, 2007;Côté, Borge, Geoffroy, Rutter, & Tremblay, 2008;Crosby, Dowsett, Gennetian, & Huston, 2010;Dearing, McCartney, & Taylor, 2009;Votruba-Drzal, Coley, & Chase-Lansdale, 2004). In the present study we build on this literature substantively and methodologically by considering (a) the degree to which such interactive effects between child care and environmental risk are evident in infancy and toddlerhood and (b) the extent to which these relations are robust to model specifications that explicitly disaggregate within-and between-child relations.…”
mentioning
confidence: 99%
“…With regard to academic problems, prior evidence indicates contemporary and longitudinal associations between higher chaos and poorer child performance of verbal and nonverbal skills that undergird scholastic problems (Berry et al, 2016;Blair, Ursache, Greenberg, & Vernon-Feagans, 2015;Deater-Deckard et al, 2009;Hanscombe, Haworth, Davis, Jaffee, & Plomin, 2011;Vernon-Feagans, Garrett-Peters, Willoughby, & Mills-Koonce, 2012). Household chaos may impede parental supervision and monitoring of child routines (including homework and studying) and parental participation in school meetings and activities.…”
Section: Chaos and Neighborhood Danger: Definitions And Theorymentioning
confidence: 99%
“…In the exercise of early parenting, dysfunctional family relationships negatively impact children, which is associated with deficits in children's cognitive and socioemotional development [20]. Specifically, different variables that influence the quality of family interactions have been identified, such as maternal depressive symptomatology and stress in parenting [21,22]; maternal emotional deregulation [23]; and experiences of early parental adversity [24,25].…”
Section: Introductionmentioning
confidence: 99%